2020
DOI: 10.3390/cancers12040858
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD44v6-Containing Isoforms Influences Cisplatin Response in Gastric Cancer Cells

Abstract: CD44v6-containing isoforms are frequently de novo expressed in gastric cancer (GC). Whether CD44v6 has a central role in GC transformation and/or progression, whether it conditions response to therapy or whether it is only a bystander marker is still not known. Therefore, we aimed to clarify the role of CD44v6 in GC. We generated GC isogenic cell lines stably expressing CD44s or CD44v6 and tested them for different cancer hallmarks and response to cisplatin, and we further confirmed our findings in cells that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Table 1 summarizes the data from published studies in which different CD44 isoforms were shown to cooperate with STAT3 in different cancer models. ( 76 79 , 81 , 83 , 86 , 87 , 89 92 )…”
Section: Cd44 and Stat3 Crosstalk In Cancermentioning
confidence: 99%
“…Table 1 summarizes the data from published studies in which different CD44 isoforms were shown to cooperate with STAT3 in different cancer models. ( 76 79 , 81 , 83 , 86 , 87 , 89 92 )…”
Section: Cd44 and Stat3 Crosstalk In Cancermentioning
confidence: 99%
“…In the stomach, we have shown that CD44v6 is considerably de novo expressed in gastric pre-malignant and malignant lesions (more than 60% of all GCs), while the normal gastric mucosa remains negative for this marker [ 14 ]. Additionally, we have recently demonstrated that CD44v6 has been correlated with poor prognosis [ 15 ] and aggressive behavior of the disease [ 16 ], suggesting its value not only for early diagnosis but also for prognosis and as a therapeutic target in GC.…”
Section: Introductionmentioning
confidence: 99%
“…Bioorthogonal Michael-addition click chemistry was employed for the site-specific conjugation of CD44v6 half-antibody to maleimide-modified PNPs. Finally, the ability of the CD44v6 half-antibody-conjugated PNPs to selectively bind to CD44v6-expressing GC cells was demonstrated using an isogenic human GC cell line, previously established and explored by our group [ 15 , 16 , 23 ]. Overall, this study provides new insights for the development of more effective GC-targeting diagnostic and therapeutic approaches and emphasizes the modular and bioorthogonal nature of our strategy that can be broadly applied to develop novel targeted approaches.…”
Section: Introductionmentioning
confidence: 99%
“…In oral cancer, CD44v4 is associated to chemoresistance to cisplatin via the activation of the MEK/ERK1/2 pathway whereas CD44v6 is associated to invasiveness via the inactivation of the PI3K/AKT/GSK3B pathway [ 118 ] as it regulates MMP-9 expression [ 119 ]. CD44v6 positive gastric cells also survive longer and have lower apoptosis after cisplatin treatment [ 120 ]. CD44 promotes tumor resistance to ROS- and chemotherapy-induced stress by regulating some of the transcription coactivators of the tumor suppressor Hippo signaling pathway that consists of a cascade of conserved kinases and transcription coactivators [ 121 , 122 ].…”
Section: Main Textmentioning
confidence: 99%